Periarticular Injection of Ketorolac Augmenting Intravenous Administration of Ketorolac for Postoperative Pain Control: A Randomized Controlled Trial in Simultaneous Bilateral Total Knee Arthroplasty - Laoruengthana, Artit; Rattanaprichavej, Piti; Mahatthanatrakul, Akaworn; Tantimethanon, Thanawat; Lohitnavy, Manupat; Pongpirul, Krit (The Journal of Knee Surgery, 2020)
Adequate postoperative pain control with minimal side effects is necessary for patients undergoing total knee arthroplasty (TKA). Ketorolac is a frequently used nonsteroidal anti-inflammatory drug due to its excellent disposition in all administration routes; however, it possesses an “analgesic ceiling,” which means that higher doses of the drug have no additional analgesic effect. Alternatively, increasing the local concentration of ketorolac via periarticular injection may provide additional pain relief to parenteral administration of ketorolac, but evidence demonstrating the benefits and safety of this approach is limited. Therefore, this study assesses whether local ketorolac injection could yield additional pain reduction to intravenous administration of ketorolac. A total of 54 patients who underwent simultaneous bilateral TKA were enrolled. Randomization was performed to determine whether 50 mg of bupivacaine plus 30 mg of ketorolac (ketorolac group), or only 50 mg bupivacaine (bupivacaine group) would be periarticularly injected into the first knee operated on (more painful), and then the contralateral knee would receive another mixture. Ketorolac (30 mg) was intravenously given every 8 hours for the first 48 hours. Visual analog scales (VASs) were used to assess pain, knee recovery function, and patients' preferred knee. Postoperative VAS pain scores in the ketorolac group were lower than those in the bupivacaine group 6 to 96 hours postoperatively and reached statistical significance 12 (4.25 ± 2.38 vs. 5.06 ± 2.48, respectively; p = 0.04) and 24 hours (4.22 ± 1.94 vs. 5.30 ± 2.12, respectively; p < 0.01) postoperatively. The ketorolac group had higher degrees of knee flexion and straight leg raise. No patient experienced adverse effects of ketorolac. On the day of discharge, 61.11% of the patients favored the knee that received local ketorolac injection (p < 0.01). Adjunct local ketorolac injection to systemic administration is well tolerated and may improve its analgesic effect as determined by the patients' perception.
Keywords: simultaneous bilateral total knee arthroplasty; periarticular injection; nonsteroidal anti-inflammatory drug; ketorolac; analgesic ceiling